2014
DOI: 10.5185/amlett.2014.amwc.1022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization And Mesomorphic Properties of Side Chain Liquid Crystalline Oligomer Having Schiff Base Type Mesogenic Group

Abstract: A new liquid crystalline oligomer OLC was synthesized from its monomer having Schiff-base type mesogenic group MLC via free radical polymerization. The chemical structures of all compounds were confirmed using UV, FTIR, 1 H NMR, 13 C NMR and MS spectroscopy. Schiff-base type thermotropic system based on side chain oligomer containing long aliphatic branching was studied to determine the change in mesophase behaviour of the Schiff-base type mesogenic groups. A combination of differantial scanning calorimetry (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The electron-donating compound, A , the CH(CH 3 ) 2 substituent, exhibits an SmA phase with a thermal stability range of 24.1 °C, while the unsubstituted derivative B has a smectic phase with a range of 20.1 °C and a low melting temperature of 67.3 °C. It was reported in [13] that the dipole moment of the mesomeric portion of the molecule impacts the type and stability of the mesophase produced, which is dependent on the attached terminal polar substituent and the steric one that varies according to size. The halogen substituent at the terminal position showed strong influence on the mesomorphic behavior of the Schiff base molecules [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron-donating compound, A , the CH(CH 3 ) 2 substituent, exhibits an SmA phase with a thermal stability range of 24.1 °C, while the unsubstituted derivative B has a smectic phase with a range of 20.1 °C and a low melting temperature of 67.3 °C. It was reported in [13] that the dipole moment of the mesomeric portion of the molecule impacts the type and stability of the mesophase produced, which is dependent on the attached terminal polar substituent and the steric one that varies according to size. The halogen substituent at the terminal position showed strong influence on the mesomorphic behavior of the Schiff base molecules [30].…”
Section: Resultsmentioning
confidence: 99%
“…Several Schiff base mesogenic homologous series of a low molar mass and twist-bend nematic phase have been investigated [10,11,12]. Many of these studies have reported to show the effect of the terminal substituent with either alkoxy chains or polar compact substituents [13]. The proper selection of a mesogenic moiety, terminal groups, and flexible wings are the essential criteria for designing new thermotropic liquid crystal materials with new phase transitions [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, LCPs with side salicylaldimine fragments were prepared by free‐radical polymerization of the corresponding monomers 5‐(10‐undecenyloxy)‐2‐[[(4‐(hexyloxy) phenyl) imino] methyl] phenol and 5‐(10‐undecenyloxy)‐2‐[[(4‐(hexyl) phenyl) imino] methyl] phenol . Modified polyguanidines, characterized by liquid crystal properties (chirality, homogeneity of the length of side chains, binding of mesogens with side chains) are of interest …”
Section: Liquid Crystal Chelating Polymersmentioning
confidence: 99%
“…These modifications in the properties of the LCs may be beneficial for mesomorphism as well as the physical properties necessary for technical uses. Schiff base linkages have been broadly employed in the preparation of numerous LC derivatives [ 14 , 15 , 16 , 17 ]. Most reports are focused on Schiff bases since the discovery of nematogenic 4-methoxybenzylidene-4′-butylaniline at room temperature [ 18 ].…”
Section: Introductionmentioning
confidence: 99%